FAKTOR YANG MEMENGARUHI RUJUKAN PASIEN PENGGUNA JKN-PBI KE FASILITAS KESEHATAN TINGKAT LANJUT DI PUSKESMAS PANCUR BATU KABUPATEN DELI SERDANG TAHUN 2019 - Diana Sinulingga; Linda Silalahi; Sulastri Br Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
BPJS complains that the puskesmas still carry out unnecessary referral actions (non-specialized diseases) to hospitals. The purpose of this study is to analyze the factors that influence the referral of PBI JKN patient patients to advanced health facilities. This is quantitative research with survey method through cross sectional approach. The research was conducted at Pancur Batu Puskesmas Deli Serdang District. The study population was 18,459 people and the sample was 186 people with purposive sampling techniques. Data analysis used univariate analysis, bivariate analysis with chi-square, and multivariate analysis using multiple logistic regression tests. The results showed that the factors that influenced were knowledge, availability of infrastructure and information about referrals, p < 0.05. Variables that do not affect are distance, motivation, attitudes of health workers, p > 0.05. The variable that has the greatest influence in this study is the variable availability of infrastructure with the value of Exp (B) / OR = 6.810 means that respondents who stated that the availability of infrastructure in hospitals was adequate, had the chance to be referred to 6.8 times higher than respondents who stated the availability of infrastructure facilities in hospitals is inadequate. It is recommended that the Pancur Batu Puskesmas repair some Puskesmas infrastructure facilities that are considered incomplete and less satisfying for some patients so that patients do not ask for referrals for diseases that can be treated at the Puskesmas.